Język i struktura Грамоты кн. Дмитрия Юрьевича в. кн. Василию Васильевичу. Problem tekstowości - Waraczewski, Maciej (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2019)
The paper analyses an Old East Slavic document – Грамота кн. Дмитрия Юрьевича в. кн. Василию Васильевичу in the context of its textuality. The language and structure of the text are described in order to prove that it can be analysed as a text in the meaning applied in modern text linguistics. Moreover, the paper shows that a wider investigation is necessary in order to prove its stylistic and genre features.